PEMBANGUNAN PARTISIPATIF DI DESA KAMPUNG PINANG KECAMATAN PERHENTIAN RAJA KABUPATEN KAMPAR TAHUN 2023 - Aini, Nurul; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Community participation–oriented village development is an important approach to achieving effective, sustainable, and locally appropriate development. This study aims to examine and analyze the implementation of participatory development in Kampung Pinang Village, Perhentian Raja District, Kampar Regency. The focus of this research is community participation in the stages of planning, implementation, and evaluation of village development. This study employs a qualitative research method with a descriptive approach. Data were collected through interviews, observations, and documentation. The research informants included village government officials, members of the Village Consultative Body (BPD), community leaders, youth leaders, and residents of Kampung Pinang Village. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that participatory development in Kampung Pinang Village has been implemented by involving the community, particularly at the planning stage through village deliberation meetings. Community participation is also evident during the implementation stage in the form of labor, material contributions, and support for village development programs. However, community participation at the evaluation stage has not been optimal, as community involvement in development evaluation forums remains limited. Therefore, efforts are needed from the village government to enhance community participation at all stages of development in order to achieve more optimal and sustainable village development. Keywords: participatory development, community participation, village development.